Complications after radical cystoprostatectomy with various variants of the heterotopic ureteroneocystostomy - A. A. Kеln (Onkourologiâ, 2021)
Background. Radical cystoprostatectomy is currently considered the most time-consuming operation with a large number of possible complications. Over the past decades, heterotopic reconstruction of the bladder using a segment of the ileum has become the optimal method of urine derivation. To date, we have successfully used a modification of V-shaped heterotopic ileocystoplasty.Objective: to compare early postoperative complications in patients who underwent radical cystoprostatectomy with the formation of a Bricker conduit and with a modified V-shaped heterotopic conduit.Materials and methods. In order to study and compare the complications that occurred in the first 30 days after surgery, we retrospectively selected patients after radical cystoprostatectomy with heterotypic ileocystoplasty. Patients were divided into two groups: 1st — patients with Bricker ileocystoplasty (n = 46), 2nd — patients with modified V-shaped heterotopic ileocystoplasty (n = 49).Results. The greatest number of complications was registered in patients of 2nd group — 19 (41.3 %), in patients of 1st group — 14 (28.6 %). Repeated surgical interventions were required in 6 (12.2 %) patients of 1st group, in 5 (10.8 %) of 2nd group. Fatal outcomes were registered in 3 (6.1 %) patients of 1st group, in 2 (4.2 %) of 2nd group. The number of pyelonephritis in the first 30 days in patients of 1st group was 8.2 %, 2nd group — 23.9 %.Conclusion. Modified V-shaped heterotopic urine derivation is easily feasible. This method should be used in patients with chronic pyelonephritis against the background of previously diagnosed ureterohydronephrosis, which is a fairly frequent consequence of the invasive nature of the growth of bladder cancer with ureteral obstruction.